Linguistic Exploration and Language Diversity in Bintuni Bay, West Papua: Sociolinguistic Study and Local Language Preservation - Saefullah, Rifki; Irman, Dede (International Journal of Linguistics, Communication, and Broadcasting, 2025)
The linguistic diversity in Bintuni Bay, West Papua, reflects the cultural richness of its people. This study identified seven languages ​​spoken by various ethnic communities in the region. Muna is the most widely spoken language and has a "Safe" status, while languages ​​such as Biak, Serui, Yapen, Numfor, and Moskona are experiencing a decline in the number of speakers, especially among the younger generation, and are facing the threat of extinction. Local languages ​​in Bintuni Bay play an important role in maintaining cultural identity, as a symbol of cultural strength, and a link with ancestors. Through in-depth interviews with local communities, it was found that local languages ​​not only function as a means of communication, but also as a means to convey cultural values ​​and traditions in traditional ceremonies. However, a number of factors influence the use of local languages, including the influence of Indonesian language education, mass media, and globalization which introduces Indonesian and foreign languages ​​as dominant languages ​​in everyday life. Socio-economic changes, as well as migration and community movement, have also accelerated language shifts. This study emphasizes the importance of preserving local languages ​​to maintain the continuity of the culture and identity of the Bintuni Bay community. The recommendations proposed include strengthening local language preservation policies, increasing the role of the younger generation in learning and using local languages, and raising public awareness of the importance of language as a cultural heritage that must be preserved.